Challenges and opportunities for improved postharvest loss measurements in plant-based food crops - Kitinoja, Lisa; Tokala, Vijay Yadav; Brondy, Amanda (Journal of Postharvest Technology, 2018)
In the last decade, the topic of food loss and waste (FLW) has acquired global attention. The Food and Agriculture Organisation (FAO) and other national and international organisations have estimated that about one-third of all the food produced and nearly half of all fruit and vegetables (F&V) are lost or wasted between harvest and consumption. Presently, abundant literature is available on the causes of postharvest losses and the technologies and practices required to manage them. However, measurements of postharvest losses of food crops are affected negatively by the use of differing definitions, scopes and ad-hoc data collection methods. Comparatively, very few studies are available on standardized measurement techniques of postharvest loss for plant-based food crops. The present review sheds light on different approaches utilized for postharvest food loss assessments and discusses existing and the opportunities available for improving food loss assessment methodologies, measurements and reporting. Detailed, standardized, high-quality information is required on the types and amount of losses at specific value chain or food supply chain points, as well as the information on the causes and sources of those losses.